A chromosomal microdeletion of 15q in a female patient with epilepsy, ID, and autism spectrum disorder: a case report. Issue 6 (12th May 2017) - Ahram, Dina F.; Al‐Sarraj, Yasser; Taha, Rowaida Z.; Elhag, Saba F.; Al‐Shaban, Fouad A.; El‐Shanti, Hatem; Kambouris, Marios
Key Clinical Message: 15q deletions have been described in association with intellectual disability and autism spectrum disorder (ASD). Previous reports have supported the role of 15q24 low copy repeats (LCRs) in mediating alternatively sized genomic rearrangements. Based on our reported finding of a 15q24 deletion coinciding with two LCR regions in a patient with epilepsy and ASD, we recommend that patients with 15q24 deletions be evaluated for ASD for early institution of therapy. Abstract : 15q deletions have been described in association with intellectual disability and autism spectrum disorder (ASD). Previous reports have supported the role of 15q24 low copy repeats (LCRs) in mediating alternatively sized genomic rearrangements. Based on our reported finding of a 15q24 deletion coinciding with two LCR regions in a patient with epilepsy and ASD, we recommend that patients with 15q24 deletions be evaluated for ASD for early institution of therapy.